Beyond Proprietorship : Murphreeís Laws on Community-Based Natural Resource Management in Southern Africa. - Mukamuri, Billy B. (Weaver Press, 2009)
Dr. Marshall Murphree is a prominent scholar in the?elds of common property theory, rural development, and natural resource management. After graduating from the London School of Economics with a doctorate in social anthropology, he returned home to Zimbabwe to work as a missionary before joining the University of Zimbabwe, where he became director, and subsequently Professor Emeritus, of the Centre for Applied Social Sciences. Beyond Proprietorship presents a range of contributions to the May 2007 conference held to honour Murphreeís work, and it conveys his central concerns of equality and.